Membumikan Hubbul Wathan Minal Iman Melalui Pembelajaran Pendidikan Agama Islam Interdisipliner - Badriyah, Laila; Nabil Akmal, Muhammad; Ilmi, Abdullah (Jurnal Ilmu Pendidikan Islam, 2025)
Hubbul wathan minal iman is an important foundation in shaping the character of a paripuna nation. The purpose of this research is to explain that hubbul wathan minal iman is part of the nation's ideological shield to maintain patriotism. Religious obedience actually motivates us to actively participate in maintaining and advancing Indonesia for the common good, instead of going against the love of the country. This research method uses Systematic literature review and analyzed using Research Collaboration Tools (Watase Uake). With a focus on Islamic religious education, interdisciplinary education. The findings of this study show that: 1. Interdisciplinary Islamic religious education offers a holistic solution by integrating the learning of Aqidah ahlak, al-quran hadith, skiing and fiqh with pkn, sociology, science. The goal is for Islamic values to be understood contextually so as to explain hubbul wathan minal iman but the principles of civilization and contribute to the progress of the nation, 2. Active and participatory learning such as collaborative projects across fields of study, contextual case studies in interdisciplinary PAI learning have the potential to provide critical space to students, building patriotism.